Building a structural model of the banking sector in the conditions of martial state in Ukraine - Ivanov, Mykola; Pylypenko, Alyona (Management and Entrepreneurship: Trends of Development, 2025)
The article is devoted to the study of the marketing activities of the banking sector under martial law in Ukraine. The purpose of the study is to develop approaches to improving marketing activities, namely, to build a structural model of the banking sector under martial law in Ukraine. In the process of preparing the article, publications on the role of the digital transformation of Ukraine as an instrument of national stability (in particular, studies by the Harvard Center for International Development and Microsoft), as well as the results of previous research in the field of banking marketing, were analyzed.An analytical review of works is presented, which considers the evolution of banking marketing and proposes a comprehensive approach to determining its essence as a philosophy, strategy and tactics of banking business. Developments that emphasize the importance of the transition from traditional to digital banking, the use of CRM systems and social networks in the marketing activities of banks are also taken into account.The paper proposes a structural model of banking marketing, which includes the policy of the National Bank of Ukraine, regional aspects of banking activities and innovative channels of interaction with customers. Macroeconomic indicators (GDP of Ukraine for 2010–2024) and ratings of leading banks of Ukraine are considered, which allows us to assess the impact of martial law on the banking system. Directions for improving banking services through expanding the functionality of mobile applications, developing offline modes and personalized chatbots are proposed.Thus, the presented work is the result of theoretical, analytical and practical research aimed at increasing the effectiveness of banking marketing strategy in crisis conditions and strengthening trust in the banking sector of Ukraine.JEL Classification: M 31, M 41